Enhancement of zein-based films for mango preservation using high-intensity ultrasound and castor oil plasticization - Fan, Xin; Chang, Lu; Pu, Huayin; Zhao, Jinghua; Wang, Huan; Wang, Yiyu; He, Wenqiang; Huang, JunRong (Ultrasonics sonochemistry, 2024)
Zein-based films exhibit high efficiency in ethylene adsorption. However, its brittleness limits the practical applications. To address this issue, this study synergizes the plasticizing effects of high-intensity ultrasound (HIU) and castor oil (CO) to reduce the brittleness of zein-based films. The plasticizing mechanism was demonstrated through the formation of new intermolecular hydrogen bonds and electrostatic interactions, as evidenced by fourier transform infrared spectroscopy (FTIR) and zeta potential measurements. The tensile strength of 6 % CO-zein film increased eightfold. Additionally, the freshness of mangoes stored with 6 % CO-zein film significantly improved, extending their shelf life from 5 days to 15 days. Therefore, this study investigated the synergistic plasticization of zein-based films through the addition of CO, based on HIU. It also provides a theoretical basis for fruit packaging.